The Influence Of Using A Sleeve Machine On The Production Cost Of Brake Shoe Products In The Die Casting Department Of PT XYZ - Kristiawan, Timotius Anggit; Wibowo, Andryana Dwiandara; Setiyawan, Trio; Indrawati, Ragil Tri (Journal of Mechanical Engineering and Applied Technology, 2024)
The process of finishing brake shoe products in PT XYZ's die casting department experienced waste using M steel shot 230 sand which reached 4,125 kg throughout 2020 and the amount of sand that fell to the floor was 36 kg per shift. The reason is that the unloading process is still manual by shaking the brake shoe jig for 2 seconds/jig then immediately pouring the brake shoe into the polybox which has holes and does not have a sand container. The use of a sieving machine is expected to reduce lost sand so that productivity can increase. The test parameters are the rotation of the motor which is regulated through an inverter of 5.5 Hz, 6 Hz, and 6.5 Hz for the time of the brake shoe sifting process, as well as the amount of sand scattered and carried by the brake shoe against the cost of purchasing sand. The results showed that productivity increased by 5.56%, the cost down of purchasing sand by up to 75.40%, and environmental cleanliness increased by 92.87%. The increase above based on Pareto analysis is included in the significant category because it meets the 20/80 rule.